A Case of Vertical Transmission of Chagas Disease Contracted via Blood Transfusion in Canada. Issue 1 (2013) - Fearon, Margaret A; Scalia, Vito; Huang, Mary; Dines, Irene; Ndao, Momar; Lagacé-Wiens, Philippe
Abstract : Chagas disease is caused by the protozoan parasite Trypanosoma cruzi and is endemic in many countries in Latin America, where infected bugs of the Triatominea subfamily carry the parasite in the gut and transmit it to humans through fecal contamination of a bite. However, vertical transmission and transmission through blood transfusion and organ transplantation is well documented. Increasing immigration from endemic countries to North America has prompted blood operators, including Canadian Blood Services and Hema Quebec, to initiate blood donor testing for Chagas antibody. In the present report, an unusual case of vertical transmission from a mother, most likely infected through blood transfusion, and detected as part of a concurrent seroprevalence study in blood donors is described.